A NEW METHOD FOR PREDICTING THERMAL-CONDUCTIVITY OF PURE ORGANIC LIQUIDS AND THEIR MIXTURES - (:unkn) unknown (CANADIAN SOC CHEMICAL ENGINEERING, 1992)
A new method based on Enskog's hard sphere theory for dense fluids and the principle of corresponding states is presented for predicting thermal conductivity of pure organic liquids and their mixtures. The thermal conductivities of alkanes, isoalkanes, aromatics, aldehydes, esters and ketones were calculated using this method which requires only critical properties and normal boiling point as input data. The predictions were compared with experimental data and other prediction methods over a wide range of temperatures (0.3 < T(r) < 0.8) and highly satisfactory results were obtained. The method was also extended to mixtures employing simple mixing rules for calculating mixture properties.
Keywords: LIQUID THERMAL CONDUCTIVITY; PREDICTING ORGANIC LIQUID THERMAL CONDUCTIVITY; BINARY